Fractional order fourier spectra in robotic manipulators with vibrations - Lima, Miguel F. M. (2019)
This paper presents a fractional system perspective in the study of signals captured during impacts and vibrations of mechanical manipulators. In order to acquire and study the signals an experimental setup was developed. The system acquires data from the sensors, in real time, and, in a second phase, processes it through an analysis package. The experimental study provides useful information that can assist in the design of a control system to be used in eliminating or reducing the effect of vibrations.